A imagem nos sites institucionais: um estudo semiótico sobre interfaces digitais interativas em ambientes hipermídia - Silva, Antonio Marcos da (2012)
The image is the subject of research in various fields of knowledge. Art history, aesthetics, anthropology, media theory, culture and iconology are some of the territories that discuss the prevalence of the image in contemporary culture, or "Picture turn" in the words of WJT Mitchell. In studies of communication and semiotics, the image is understood as a kind of sign (Santaella and Nöth). The main objective of this research is to study the role of images in the communication processes of institutional sites, discussing, specifically, issues related to the processes of creating digital interactive interfaces. How do images assist in the construction of meaning and communication effectively in an institution? The work has an interdisciplinary nature and is based on two vectors: 1 - concepts of hypermedia and digital interfaces, according to Lucia Leão, Lucia Santaella, Marcus and Engelbart, considered fundamental to the nature of this research because it is the object of analysis, 2 - Peircean semiotics for the analytical study of its empirical objects (institutional sites) in accordance with their critical commentators: Cassiano Rodrigues Terra, Roberto Chiachiri, Santaella, Colapietro, Andersen and Eco